Intergenerational views of mothers and daugthers on femaleness, feminity and the opposite sex. - Sapio, Majah Angelica V.
This is a descriptive study aimed to determine the views of mother and daughters regarding femaleness, femininity, and the opposite sex. Respondents were 13 mothers, aged 40-60, who are living with their husbands, and 13 daughters, aged 16-24, who are living with their parents. An interview guide with five sections namely, sources of information on femaleness and femininity, roles and responsibilities, concept of love, concept of sexuality, and views on reproductive health, was utilized to solicit responses. Results showed that sources of information include the family, peers, school and teachers, religion and due to exposure to technological advances, the internet. While traditional segregation of gender is still maintained, gender roles have already become flexible. Traditional beliefs on love and conservative attitudes toward sexuality are still held up to this day both by mothers and daughters despite the changes in the society. Respondents are aware of reproductive health and other concerns. All in all, mothers? and daughters? views on femaleness, femininity, and the opposite sex were mostly similar. Profound discussions on topics such as love and sexuality, and reproductive health are still generally absent at home.